2015
DOI: 10.1088/1475-7516/2015/11/044
|View full text |Cite
|
Sign up to set email alerts
|

The quantum realm of the ``Little Sibling'' of the Big Rip singularity

Abstract: We analyse the quantum behaviour of the "Little Sibling" of the Big Rip singularity (LSBR) [1]. The quantisation is carried within the geometrodynamical approach given by the WheelerDeWitt (WDW) equation. The classical model is based on a Friedmann-Lemaître-RobertsonWalker Universe filled by a perfect fluid that can be mapped to a scalar field with phantom character. We analyse the WDW equation in two setups. In the first step, we consider the scale factor as the single degree of freedom, which from a classica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 94 publications
0
32
0
Order By: Relevance
“…For the three models at hand, we can solve (A5) analytically well inside the DE dominated regime, i.e., for t ≥ t * we have H 2 ≈ (κ 2 /3)ρ d , obtaining for each case the potential [40,41,[93][94][95] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the three models at hand, we can solve (A5) analytically well inside the DE dominated regime, i.e., for t ≥ t * we have H 2 ≈ (κ 2 /3)ρ d , obtaining for each case the potential [40,41,[93][94][95] …”
Section: Discussionmentioning
confidence: 99%
“…The classical singular asymptotic behaviour of these dark energy models has led to a quantum cosmological analysis of these setups [39][40][41][42]95]. In these works, it was concluded that once the Universe enters in a genuinely quantum phase; i.e., where coherence and entanglement effects are important, the Universe would evade a doomsdayà la rip.…”
Section: Introductionmentioning
confidence: 99%
“…However, as energy density diverges in all the cases presented, one might expect that quantum effects become important at some point in the future evolution. In fact, a quantum analysis shows that in all cases, the classical abrupt event can be avoided from a quantum point of view [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Since Equation (36) is a second order differential equation, only two of the four ϕ (i) k functions given in Equation (38) are linearly independent. These functions can be written as [44,45] …”
Section: Wdw Equation With a Scalar Fieldmentioning
confidence: 99%